How Does Agriculture Change Our Climate? - Colombo, B.; West P; Smith, Pete; Tubiello, F.N.; Gerber J; Engstrom P; Urevig A; Wollenberg, Eva Karoline (2016)
Greenhouse gas emissions from agriculture reached an all-time high in 2014, and for the first time since 1960 may now outpace fossil fuel growth. The agriculture sector plays a key role in reducing global emissions to avoid dangerous levels of climate change. The short report highlights trends and the primary sources of agricultural emissions, as well as a few solutions already in practice. In this report, we consider emissions from just part of the global food system: deforestation and agricultural management. The share of emissions from transportation of products in the global food supply chain, packaging, and food waste, for example, are important but not included here. When these activities are also considered, the global food system accounts for roughly 30 percent of global emissions.